Cross-sectional study of factors affecting the receipt of mental health education in older migrants in China - Wanchen Wang; Jia Song; Chengxin Fan; Qiusha Li; Dongping Ma; Wenqiang Yin (BMC, 2023)
Abstract Background Population migration in China has increasingly included middle-aged and older populations. Relatedly, the lack of mental health education among China's older migrants is still an important but neglected problem. This study aimed to understand the current situation of mental health education received by the older migrant population in China and to explore related influencing factors. Methods This cross-sectional study included 5729 older migrants who participated in the 2017 China Migrants Dynamic Survey. The independent variables included four components: demographic and socioeconomic characteristics, migration factors, public health service utilization, and social integration factors. Data were analyzed using the chi-square test for single factors and a binary logistic regression model for multiple factors. Results A total of 1749 older migrants received mental health education, for a receipt rate of 30.53%. Regression analysis showed that older migrant individuals who had an average monthly household income > 3000 CNY, self-rated their health as healthy, had chronic diseases, had heard of National Basic Public Health Services, had established health records, received ≥2 types of health education were willing to integrate into the local population, and were highly involved in the community were more likely to receive mental health education. Older migrants who were ≥ 70 years old, had an elementary school education or below, had difficulties in the local community, had migrated ≥11 years prior, moved for their offspring, and moved across provinces were less likely to receive mental health education. Conclusions The older migrant population does not receive sufficient mental health education. Mental health interventions should be tailored to the characteristics of older migrants to increase their mental health literacy and meet their psychological needs.